ELECTRONIC STRUCTURES AND REACTIVITY OF EIGHT MIXED-LIGAND COMPLEXES OF CALCIUM ACETATE BY A QUANTUM-CHEMICAL METHOD - Jurayeva Umida Boxodir kizi, Turakulov Jakhongir Ulugbekovich, Norbutayeva Kanoat Pulatovna, Kenjaeva Munavvarbonu Abdumannon kizi, Tukhtamurodova Zilola Khamidjon kizi (Zeta Repository, 2023)
In the present work, the results of calculations of the electronic structure of eight mixed-amide complex compounds of calcium acetate with semi-empirical PM3 methods using the molecular orbital method are carried out, and the energy characteristics of eight new coordination compounds are compared. The calculations were carried out by the semi-empirical PM3 method in the Hyper-Chem.8-07 software package.